Analysis of the occurrence of accidents involving venomous animals in the Municipality of Caxias, state of Maranhão, Brazil (Research, Society and Development, 2020)
This article aimed to determine the prevalence of accidents involving venomous animals in the city of Caxias-MA in the period from 2016 to 2019. It is a descriptive, documentary, retrospective study, with a quantitative approach, carried out in the period from 2016 to 2019 , having as universe of data notifications of accidents with venomous animals in the city of Caxias-MA. Data were collected through the disease information and notification system (SINAN) made available by the Ministry of Health. Regarding the results, a study evaluated 997 reported cases of accidents involving venomous animals in the city of Caxias-MA, in the period from 2016 to 2019, as for the profile of the identified individuals, there was a prevalence of males (55.97%), age group of 20 at 59 years old (59.88%), education of the injured was incomplete elementary school (37.41%), most were brown (92.38%), with the highest number of occurrences in 2018 (32.60%), most accidents involve scorpions, (59.98%). As for the species of snakes, Crotalus was the most prevalent (59.76%), the time of attendance after the bite occurred between one to three hours after the accident (50.65%) of the records. The study allowed analyzing the prevalence of accidents involving venomous animals during a time frame (2016 to 2019), in which an increase in the number of cases and a small oscillation over the years were observed. In this regard, nursing plays an important role in the prevention of these diseases, since it is constantly in contact with patients who seek hospital care.